Human Capital Management of Government Internal Supervisory at the Ministry of Defense of the Republic Indonesia - Efendi, Afwan; Purwana, Dedi; Buchdadi, Agung Dharmawan (Bright Institute, 2022)
The results of the study found that the government internal supervisory performance was not yet optimal in supporting the achievement of the vision and mission as well as organizational goals. This study aims to provide an overview of human capital management practices of government internal supervisory at the Ministry of Defense by using a balanced scorecard perspective approach from a stakeholder perspective, a business internal process perspective, a learning and growth perspective and a financial perspective. This study used a qualitative method with a case study approach and used purposive and snowball sampling. There are 19 informants including a structural officer, the auditor, and personnel from the National Financial and Development Supervisory Board. It is noted that the quality of the auditors does not fulfill the required quality. The recommendations include the importance of improving aspects of human resource competence through education and training for certification of the Functional Auditor (JFA) according to the level of the position, improving the quality of the code of ethics, improving the recruitment system, and increasing the budget for providing the operational budget and enhancing the quality of the government internal supervisory.